LITERATURE REVIEW: APLIKASI PENANDA MOLEKULER UNTUK ANALISIS KEANEKARAGAMAN GENETIK HEWAN - Mudaningrat, Ajeng; Umaya, Flora; Syahriza, Farah Ayu Afdhila; Anggraito, Yustinus Ulung; Setiati, Ning (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: Molecular markers (DNA markers) are DNA sequences that are easily detected to characterize or detect certain genetic diversity, one of which is in animals. There are various marker systems used with their respective characteristics. Some of the molecular markers include RFLP, RAPD, ISSR, SSR, and SNP. The purpose of this study was to analyze genetic diversity in animals using molecular marker applications.Methods: The method used is literature review using reputable national and international journals.Results: Based on the results of a literature review, the genetic diversity of various species such as catfish, deer, tilapia, crabs, seahorses, ducks, cattle and buffaloes can be analyzed for genetic diversity using various molecular markers either by using PCR-RFLP, RAPD, ISSR, SSR, or SNPs.Conclusion: The application of molecular markers can be used to analyze animal genetic diversity.